Smartphone application improves fertility treatment-related literacy in a large-scale virtual randomized controlled trial in Japan - Ryo Yokomizo (Nature Portfolio, 2021)
Abstract People of reproductive age have unmet needs related to deficiencies in fertility literacy. Here, we aimed to investigate whether providing fertility-related information via a smartphone application could improve fertility treatment-related literacy in participants. We performed a randomized control-group pretest posttest study and recruited participants between June 18 and 25, 2020. Participants’ fertility treatment-related literacy was assessed with a pretest that comprised of 28 questions and participants were allocated with stratified randomization to either intervention group or control group. The intervention comprised a one-week smartphone application-based provision of information on fertility-related information and the control group received general information about women’s healthcare. Effectiveness of intervention was assessed using a posttest. A total of 4137 participants were administered the questionnaire and pretest, among which 3765 participants (91.0 %) responded and were randomly allocated into either the intervention group (N = 1883) or the control group (N = 1882). A significantly higher posttest mean score was observed for the intervention group compared to the control group (P = 0.0017). We also observed that posttest scores were significantly improved compared to pretest scores in both the intervention and control group (P < 0.001). When examining by specific test question, the proportion answering correctly increased at posttest compared to pretest for both intervention and control groups (P < 0.001). Furthermore, the intervention group showed a greater mean difference between posttest and pretest scores than the control group (P < 0.001). In conclusion, educational intervention using a smartphone application contributed to enhancing fertility treatment-related literacy.